The Influence of Social Media Marketing Through Instagram on Consumer Purchase Decisions of Lokanata Coffee the City of Tasikmalaya - Agustian, Tito; Fauziyah, Azizah; Yusuf, Ismail (A Social Science and Entrepreneurship Journal, 2022)
The purpose of this study was to the influence of social media marketing through Instagram on consumer purchase decisions of Lokanata Coffee the City of Tasikmalaya. The object of this research is Lokanata Coffee which is located on Jl. AH Nasution No. 297b, Cipari, Kec. Mangkubumi, Tasikmalaya City. The objectives of this study are: (1) To find out the general description of social media marketing, (2) To find out the general description of purchasing decisions, (3) To determine the effect of social media marketing on consumer purchasing decisions of Lokanata Coffee. The method used is a quantitative method with a descriptive and verification approach. The data collection technique used a questionnaire in the form of a google form with a Likert scale. The regression coefficient value is 0.776 so that the influence of social media marketing on consumer purchasing decisions for Lokanata Coffee is positive or influential. The significance value of social media marketing is 0.00t1 0.05 and tcount ttabel (9.867 1.986) so that Ha is accepted and Ho is rejected.